1991
DOI: 10.1099/0022-1317-72-9-2239
|View full text |Cite
|
Sign up to set email alerts
|

Outer capsid protein heterogeneity of rice dwarf phytoreovirus

Abstract: The 46K outer capsid protein encoded by RNA segment $8 and the 42K polypeptide, previously thought to be the segment S9-encoded structural protein, were isolated from a rice dwarf phytoreovirus purified preparation, and then analysed by peptide mapping and electroblot-ELISA. Staphylococcus aureus V8 protease peptide mapping patterns of the 42K and 46K proteins were similar. Two monoclonal antibodies (MAbs), obtained after immunization with virus particles dissociated by 0.1% SDS, were each specific for both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
1

Year Published

1993
1993
1998
1998

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
1
3
1
Order By: Relevance
“…However, we showed previously that the 39 k protein was not the S9-coded product but a product overlapping with the 43 k, S8-coded, outer capsid protein [18]. The present study revealed that $9 encodes a protein with an apparent Mr of 49 k, larger than that of P8.…”
contrasting
confidence: 68%
See 2 more Smart Citations
“…However, we showed previously that the 39 k protein was not the S9-coded product but a product overlapping with the 43 k, S8-coded, outer capsid protein [18]. The present study revealed that $9 encodes a protein with an apparent Mr of 49 k, larger than that of P8.…”
contrasting
confidence: 68%
“…Treatment with such organic solvents is considered to result in loss of the amorphous outer protein layer but not loss of the outer capsids [1,14]. The conclusion reached from the present and previous studies [18] is, therefore, that RDV P9 is not an outer capsid protein but a nonstructural protein. In addition to P9 stated above, P4, P6, and P10 are considered to be nonstructural proteins.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…They have been classified into three different groups, Phytoreovirus, Fijivirus and the rice ragged stunt virus (RRSV) group (possible genus), based on particle morphology, number of dsRNA genome segments and vector species (Boccardo & Milne, 1984;Francki et al, 1985). Recent genomic analyses of wound tumour virus (WTV) genome segments 4 to 12 (Asamizu et al, 1985;Anzola et al, 1987Anzola et al, , 1989aXu et al, 1989;Dall et al, 1989), rice dwarf virus (RDV) genome segments 3 to 11 (Uyeda et al, 1987a(Uyeda et al, , 1989(Uyeda et al, , 1990aOmura et al, 1988Omura et al, , 1989Yamada et al, 1990;Suzuki et al, 1990a, b;Suzuki & Sugawara, 1991) and rice gall dwarf virus genome segments 8 to 10 (Koganezawa et al, 1990;Noda et al, 1991) revealed molecular relationships between the viruses within the genus Phytoreovirus. These three viruses were found to share a conserved terminal oligonucleotide sequence (Asamizu et al, 1985;Kudo et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…reoviruses: wound tumor virus (WTV) genome segments 4 to 12 [23], rice dwarf virus (RDV) genome segments 1 to 12 [28][29][30][31][32]35], rice gall dwarf virus (RGDV) genome segments 8 to 10 [14,22], maize rough dwarf virus (MRDV) genome segment 6 [18], and rice black-streaked dwarf virus (RBSDV) genome segments 7, 8 and 10 [1,33]. To date the only nucleotide sequence information about RRSV is confined to the 5' and 3' termini (5' G A U A A A ---and ---G U G C 3') which was obtained by direct R N A sequencing [39].…”
Section: Introductionmentioning
confidence: 99%